(untitled) (Al-Academy, 2025)
The relationships and interconnections between adjacent or divergent fields of knowledge have often constituted qualitative additions to human knowledge and contributed to the crystallization of new scientific/humanitarian maps, paths, and scopes that benefit and delight the details of daily life, as well as creating broader and more open cultural climates. The importance of the research lies in its shedding a bright light on the growing potential of artificial intelligence technology and its applications in cinema and television. The aim of this study was to reveal the ways in which artificial intelligence technology is employed to generate aesthetic environments in cinematic and television artworks. The theoretical framework included two chapters: the first: artificial intelligence: the essence and concept, from process to becoming; and the second: artificial intelligence and its operations in generating visual discourse environments. The third chapter included the research methodology and the research sample, as well as sample analysis. The research concluded with the results, conclusions, recommendations, and a list of sources